GAMBAR ILUSTRASI BUKU CERITA ANAK-ANAK SEBAGAI PELESTARIAN DAN PENGEMBANGAN BUDAYA DI ERA GLOBALISASI - Kristanto Kristanto (Universitas PGRI Semarang, 2011)
Rapidly changing time is makeresponsiveteaching methodsshould be increasinglyinnovative.It's alsoapushfor theeducatorsto be vigilantin the face ofunderstanding the value- the valueas opposedtostudentsandyoung peopleespeciallyvalue- the value ofarts and cultureshouldprospectivelybepreserved andattached to theinspirationof future generations. The methodiseasilystimulatedand responded toby the younger generationis throughillustration, because it isvisual, can be seen, komonikatif, informativeandeasy to understand. From an early age, children need to beequipped with alearningculture throughchildren's storybooks-childrenwhoareIllustrativeasinvestmentvalue- the value ofculturein children-childrenwhocan protectthemselvesandrespondto thechallenges ofglobalizationbothpresentand future.